2006
DOI: 10.1111/j.1460-9568.2006.04783.x
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin3A regulates synaptic function of differentiated hippocampal neurons

Abstract: Semaphorins are major chemorepellents for developing neuronal projections. Their persistent expression at adult stages suggests that they may contribute to the functioning of neuronal circuits. We investigated the functional properties of semaphorin3A (Sema3A) in adult hippocampal neurons, and report that exogenous application of this cue decreases the efficacy of synaptic transmission evoked in the CA1 region of hippocampal slices. In situ hybridization, imaging and biochemical techniques showed that the Sema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 54 publications
(66 reference statements)
3
55
0
Order By: Relevance
“…Sema3A Binds to CS-E in PNNs-Sema3A is a potent regulator of neurite growth (22) and cell migration (40) in the developing nervous system, and it has strong effects on synapse dynamics (15)(16)(17). Cell surface retention of Sema3A has been observed on Neuro-2a cells, from which it is released by ChABC treatment or an addition of CS-B or heparin; this implicated A and B, full-length Sema3A-GFP recovered from cell lysate binds to heparin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sema3A Binds to CS-E in PNNs-Sema3A is a potent regulator of neurite growth (22) and cell migration (40) in the developing nervous system, and it has strong effects on synapse dynamics (15)(16)(17). Cell surface retention of Sema3A has been observed on Neuro-2a cells, from which it is released by ChABC treatment or an addition of CS-B or heparin; this implicated A and B, full-length Sema3A-GFP recovered from cell lysate binds to heparin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of Sema3A persists at a considerable level in parts of the CNS into adulthood (23). Its presence affects synapse dynamics (15,17) and may influence plasticity in the mature CNS (22). An interaction between CS and Sema3A has been previously reported in vitro in neuronal cell culture (25) and also by co-localization studies of CSPG and Sema3A during development in vivo (26).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…94 To elucidate the significance of CRMP2 phosphorylation in the pathogenesis of Alzheimer disease, CRMP2 phosphorylation-deficient knock-in (crmp2 ki / ki ) mice were generated in which the serine residue at 522 of the protein was replaced with alanine. Intracerebroventricular injection of Ab [25][26][27][28][29][30][31][32][33][34][35] peptide, a neurotoxic fragment of Ab protein, in wild-type mice increased hippocampal phosphorylation of CRMP2. Behavioral assessment revealed that the injection of the Ab [25][26][27][28][29][30][31][32][33][34][35] peptide caused impairment of both cognitive function and long-term potentiation in wild-type animals, but not in crmp2 ki / ki mice.…”
Section: Distinct But Overlapping Roles Of Neurotrophins and Semaphorinsmentioning
confidence: 99%
“…However, the type3 semaphorins could be a negative regulator of spine development, synaptic structure and synaptic transmission. [27][28][29] Kolodkin and his colleagues demonstrated that the Sema3F ¡ / ¡ , Nrp2 ¡ / ¡ and PlexA3 ¡ / ¡ mice, exhibited increased dentate gyrus (DG) granule cell (GC) and cortical layer V pyramidal neuron spine number and size as well as aberrant spine distribution. 27 In dissociated neurons in vitro, Sema3F promotes loss of spines and excitatory synapses.…”
Section: Background: Dendritic Development Regulated By Semaphorinsmentioning
confidence: 99%